Human ACE gene polymorphism and distilled water induced cough. Issue 2 (February 1997) - Morice, A H; Turley, A J; Linton, T K
Abstract : BACKGROUND: Inhibitors of angiotensin converting enzyme (ACE) cause a non-productive cough. The insertion/deletion polymorphism of ACE was used as a genetic marker to investigate the relationship between ACE genotype and cough sensitivity. METHODS: A double blind cough challenge was performed in 66 normotensive subjects (34 men) of mean age 34.8 years (range 18-80) using aerosols of distilled water. The number of coughs during the one minute exposure to water was recorded. DNA samples from venous blood were amplified by the polymerase chain reaction and resolved on a 1% agarose gel. They were analysed for the presence of a polymorphism in intron 16 of the ACE gene consisting of an insertion (I) or deletion (D) of an Alu repetitive sequence 287 base pairs long. RESULTS: The distribution of genotypes was 20 II, 26 ID, and 20 DD. The cough response was significantly (p < 0.01) related to the ACE genotype, the mean number of coughs being 15.8, 11.3, and 9.6, respectively, in subjects with the II, ID, and DD genotypes. CONCLUSIONS: The observation that cough challenge is dependent on ACE genotype in normal subjects is evidence of a link between ACE activity and the cough reflex.